What do students expect from the English Medium Instruction in Physical Activity and Sport Sciences? - Anna Szczesniak; Elvira Barrios (Revista de Lenguas para Fines Específicos)
The rising popularity of English Medium Instruction (EMI) in higher education has become a notable global trend. However, there is limited information on what students expect from these programmes. Therefore, this study aims to explore students’ expectations of EMI within a Physical Activity and Sport Sciences degree at a (removed for anonymous issues) public university, the first such programme in (removed for anonymous issues). It also examines the relationship between EMI expectations and students’ profile variables such as gender, accredited and perceived English proficiency, and prior experience in bilingual education. Data was collected from a sample of 109 students using the English Medium Instruction Expectations Scale, which has been validated for reliability and validity. Results showed high expectations for improved job opportunities and linguistic competence, particularly in technical vocabulary and comprehension skills, with lower expectations for written expression. However, students anticipated their academic achievement to be less effective compared to instruction in Spanish. Additionally, female students and those with higher accredited English levels had significantly higher expectations regarding job prospects. In conclusion, this study underscores the importance of understanding students’ expectations of EMI programmes to identify gaps between anticipated and actual experiences, as these mismatches can impact satisfaction and perceptions of the programme effectiveness.